Transglossic Language Practice of Generation Z on Instagram in Indonesia - Anggi Purwa Lestarina (ENLIT, 2022)
The research investigated how Indonesia's generation Z used social media to practice their language. The way ideology was constructed in linguistic variations and underlying the language in the online context. The paper's goal was to comprehend sociolinguistic dynamics by looking at the scientific reasons for youth language use and to raise awareness about language and social conditions of generation Z. According to the Tranglossic framework as propounded by Sultana et al. (2015) for an in-depth understanding of contextual (physical location and participants), pretextual (historical trajectory texts), subtextual (ideologies mobilized by the text), intertextual (meanings that occur across texts), post textual interpretation of the data (the way texts are read, interpreted, resisted, and appropriated) and interview conducted to two accounts of Instagram users. As a result, generation Z was the creative speakers and critical thinker in social media because they built the ability of complex encoding. The complex encoding was related to their social attribution in detail of affiliation with a certain community, regional identity, national identity, a desire as the part of a world citizen, religion, popular culture, and education.